2022
DOI: 10.1093/bjs/znac266
|View full text |Cite
|
Sign up to set email alerts
|

Development and external validation of DISPAIR fistula risk score for clinically relevant postoperative pancreatic fistula risk after distal pancreatectomy

Abstract: Background Highly utilized risk scores for clinically relevant postoperative pancreatic fistula (CR-POPF) have guided clinical decision-making in pancreatoduodenectomy. However, none has been successfully developed for distal pancreatectomy. This study aimed to develop and validate a new fistula risk score for distal pancreatectomy. Methods Patients undergoing distal pancreatectomy at Helsinki University Hospital, Finland fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 42 publications
0
35
1
Order By: Relevance
“…Several studies have identified risk factors related to POPF occurrence after DP. (7,8). Effective closure of pancreatic remnants of irregular thickness is crucial for fistula prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified risk factors related to POPF occurrence after DP. (7,8). Effective closure of pancreatic remnants of irregular thickness is crucial for fistula prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pancreatic fistula (POPF) remains the major complication after DP and can potentially cause further complications, such as abdominal fluid collection, severe intra-abdominal infection and hemorrhage. Preventing POPF via effective pancreatic remnant closure remains challenging, and no consensus on the optimal surgical technique has been established (1,(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Area under the receiver operating characteristic curve will be used to assess discrimination. Validation of the model will be performed as the methods of Bonsdorff et al [ 16 ]. Statistical analysis will be completed using R (R Foundation Statistical Program).…”
Section: Methodsmentioning
confidence: 99%
“…The clinical relevance of pancreas thickness in risk assessment of POPF after DP should be underlined. While intuitively meaningful, this was rarely reported in previous published studies (2,8,9). Such a point raises questions regarding the appropriate definition of a thick pancreas and which transection technique should be preferred (10).…”
mentioning
confidence: 87%
“…The authors should be commended for this study bringing the first validated risk score for CR-POPF after DP, the so-called D-FRS. Recently, another similar score has been published but without external validation ( 2 ). Such a clinical risk score is of paramount importance for preoperative risk assessment and patient information.…”
mentioning
confidence: 99%